2017
DOI: 10.1186/s40543-017-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental characterization of organic wastes for evaluation of vermicompost maturity

Abstract: Instrumental analysis of vermicompost with the help of modern technologies provides essential information on its maturity, before it can be used for agricultural application. Nowadays, vermicompost is considered as a promising organic alternative to chemical fertilizers in agriculture and horticulture. The objectives of this review are to summarize the sophisticated instrumental techniques such as scanning electron microscopy (SEM), fourier transform infrared (FT-IR) spectroscopy, thermogravimetry (TG), ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 70 publications
(84 reference statements)
2
31
0
2
Order By: Relevance
“…During vermicomposting, the earthworms (Eisenia fetida) ingested and pulverized the initial waste mixture in the gizzard (Ali et al, 2015). Further disintegration of substrate material was assisted by different enzymes and enteric microbial activities mainly by hydrolytic bacteria present in the earthworm's gut (Arancon et al, 2005;Bhat et al, 2017). Our results are in consistence with Unuofin and Mnkeni (2014), who observed fine granular structure of vermicomposts produced from cow dung and paper waste mixtures.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 78%
See 2 more Smart Citations
“…During vermicomposting, the earthworms (Eisenia fetida) ingested and pulverized the initial waste mixture in the gizzard (Ali et al, 2015). Further disintegration of substrate material was assisted by different enzymes and enteric microbial activities mainly by hydrolytic bacteria present in the earthworm's gut (Arancon et al, 2005;Bhat et al, 2017). Our results are in consistence with Unuofin and Mnkeni (2014), who observed fine granular structure of vermicomposts produced from cow dung and paper waste mixtures.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 78%
“…Thermogravimetry (TG) is a thermal technique which is used to examine the changes in mass of a sample at increasing temperature and constant heating rate. TG analysis of substrate material at two-time intervals during vermicomposting revealed thermal stability of samples explained by mass loss due to dehydration, oxidation and degradation (Bhat et al, 2017;Khatua et al, 2018). The derivative thermogravimetric (DTG) curves were found from the first derivative of thermogravimetric profiles.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cherif et al (2009) and Gwenzi et al (2015) assessed the effectiveness of MSW application on agricultural soil in northern Africa arid climate and recommended using MSW compost at a rate of 40 Mg/ha to fertilize wheat crops. Many researchers (e.g., Abbasi and Gajalakshmi 2015;Bhat et al 2017;Sarkar and Chourasia 2017;Chaturvedi and Verma 2015) suggested adding different kinds of bacteria to improve the speed and quality of composting processes. Abbasi and Gajalakshmi (2015), for example, used termites to decompose substances which resist composting, vermin composting, or anaerobic digestion such as cotton waste, coconut shells, and torn jute bags.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo a partir de los 60 días fue disminuyendo, como se observa en la figura 4. Esta disminución del C orgánico durante el proceso de vermicomposteo sugiere que la degradación de la materia orgánica, (mineralización y madurez de la misma), es llevada a cabo por la lombriz de tierra y microorganismos, que de manera conjunta la utilizan como alimento y fuente de energía para el desarrollo de sus actividades bioquímicas, lo que concuerda con Amouei et al (2017) y Bhat et al (2017). Se sabe que la pérdida de la materia orgánica puede llegar hasta un 49 % debido a la actividad respiratoria de las lombrices y microorganismos (Deka et al 2011), que junto a la actividad enzimática favorecen la descomposición y reducción de los residuos orgánicos.…”
Section: Resultados Y Discusiónunclassified